Strategi Pemasaran Berbasis Nilai-Nilai Entrepreneurship dalam Meningkatkan Investasi di PHRI Kabupaten Bandung - Dinihayati, Erti; Erlangga, Heri; Camelia, Mela; Dewinta, Rima (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The main objective of this research is to identify and apply entrepreneurial values in marketing strategies to enhance investment in the hospitality and restaurant sector in Bandung Regency. The findings indicate that entrepreneurial values such as innovation, proactivity, calculated risk-taking, creativity, commitment to quality, collaboration, networking, and adaptability are crucial for effective marketing strategies. Strategies based on these values have proven capable of attracting investor attention and improving the competitiveness of the hospitality and restaurant sector in Bandung Regency. Innovation in products and services, proactivity in marketing, and a commitment to quality are key factors in attracting investment. The implementation of marketing strategies rooted in entrepreneurial values positively impacts investment growth and helps build the reputation and credibility of the Indonesian Hotel and Restaurant Association (PHRI) in Bandung Regency in the eyes of investors. The use of digital technology and social media in marketing strategies plays an important role in reaching a broader audience and attracting investor interest, enabling real-time measurement of marketing campaign effectiveness and strategy adjustments based on collected data. Recommendations for PHRI Bandung Regency include strengthening branding and innovation, enhancing collaboration and networking, optimal use of digital technology, continuous evaluation and adjustment, and improving quality and services. By applying these recommendations, it is hoped that marketing strategies based on entrepreneurial values will continue to develop and provide a sustainable positive impact on the hospitality and restaurant sector in Bandung Regency, increase investment, and reinforce Bandung Regency's position as a premier tourist destination.